JOB DEMANDS OF POLICE PERSONNEL: IDENTIFYING THEMES AND RESEARCH CLUSTERS FROM BIBLIOMETRIC ANALYSIS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
licing is the only arm of the state that  is authorized to use coercive force against  its citizens, which makes the job uniquely  demanding. With the emergence of a work  culture characterized by job demands with  complex technology, work overload, social  isolation, sleep disturbances, and spillover effects  leading to work-life imbalance, police work has  been identified as one with a highly stressful  environment. Despite interest over the years in  the predictors and outcomes of police stress, the  research findings are inconsistent. No review,  to date, has offered a holistic retrospection on  the job demands of the police. The current  study is an attempt to overview job demands  research on police personnel using bibliometric  analysis and systematic review of literature. The  study highlights the publication trend, the most  productive and influential authors, the significant  areas of research in the domain, and infers the  intellectual structure of job demands research  on police personnel. Using the science mapping  techniques of co-citation and bibliometric  coupling analyses, the study infers the knowledge  foundation and the thematic structure of job  demands research in police personnel for the  period 1983-March 2024 by uncovering six  and eight specific areas of job demands research  on police personnel respectively. Additionally,  by using co-occurrence analysis, the study also  attempts to highlight the influential topics of  research in the same period divided into four  segments and also outlines the future research  directions in the domain of job demands with  police personnel as the focal point.
Keywords: A Bibliometric Analysis Review